Pre-Operative Assesment of Lymphocyte Monocyte Ratio in Ovarian Neoplasms - Kumar K.T, Athulya Krishna; Upadhyaya, Krishnaraj; Nair, Vineeth G (Annals of Pathology and Laboratory Medicine, 2018)
Background: Inflammation has been shown to have a prognostic role in a variety of cancers. The objective of this study was to evaluate lymphocyte monocyte ratio and neutrophil lymphocyte ratio in both benign and malignant ovarian neoplasms. Materials and methods: A total of 77 cases of ovarian neoplasms fitting our inclusion criteria were retrospectively reviewed. Clinicopathological data of the patients were analysed. The absolute blood counts of neutrophils, lymphocytes and monocytes, were collected and used to calculate the neutrophil-to-lymphocyte ratio (NLR) and lymphocyte to monocyte ratio (LMR). The optimal cut-off value of the LMR was determined by using receiver operating characteristic curve analysis and Youden’s index. Results: Analysis revealed that benign ovarian neoplasms were statistically associated with a higher LMR when compared to malignant ovarian neoplasms (p = 0.023). A receiver operating characteristic curve analysis was performed and the area under the curve was 0.659. The optimum cut-off for LMR, calculated using Youden’s index, was determined to be 6.25, which has a relatively high sensitivity of 87.5% but a less than desirable specificity of 44.4%. No significant statistical association was found between LMR and NLR with the other clinicopathological variables. Conclusion: Our study indicates that lymphocyte monocyte ratio may serve as an important biomarker in the differentiation of benign and malignant ovarian neoplasms. However, further studies are warranted to confirm this conclusion.